2018
DOI: 10.1002/psc.3117
|View full text |Cite
|
Sign up to set email alerts
|

An amphipathic cyclic tetrapeptide scaffold containing halogenated β2,2‐amino acids with activity against multiresistant bacteria

Abstract: The present study describes the synthesis and biological studies of a small series of head-to-tail cyclic tetrapeptides of the general structure c(Lys-β -Xaa-Lys) containing one lipophilic β -amino acid and Lys, Gly, Ala, or Phe as the Xaa residue in the sequence. The peptides were investigated for antimicrobial activity against gram-positive and gram-negative reference strains and 30 multiresistant clinical isolates including strains with extended spectrum β-lactamase-carbapenemase (ESBL-CARBA) production. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…A recent study has described the incorporation of two halogenated α,α-disubstituted β 2,2 -amino acid residues [ 218 ] into an amphipathic cyclic tetrapeptide [ 219 ] ( Figure 8 ) with general sequence c(Lys-β2,2-Xaa-Lys), where Xaa = Lys, Gly, Ala, or Phe. Antimicrobial activity was in the low μg/mL concentration range against multi-resistant Gram-(+) and Gram-(-) strains, with little toxicity against human red blood cells, in particular for the halogenated analogues c(Lys-β 2,2 (4-CF 3 )-Phe-Lys) and c(Lys-β 2,2 (3,5-di-CF 3 )-Gly-Lys).…”
Section: Halogenated Ampsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has described the incorporation of two halogenated α,α-disubstituted β 2,2 -amino acid residues [ 218 ] into an amphipathic cyclic tetrapeptide [ 219 ] ( Figure 8 ) with general sequence c(Lys-β2,2-Xaa-Lys), where Xaa = Lys, Gly, Ala, or Phe. Antimicrobial activity was in the low μg/mL concentration range against multi-resistant Gram-(+) and Gram-(-) strains, with little toxicity against human red blood cells, in particular for the halogenated analogues c(Lys-β 2,2 (4-CF 3 )-Phe-Lys) and c(Lys-β 2,2 (3,5-di-CF 3 )-Gly-Lys).…”
Section: Halogenated Ampsmentioning
confidence: 99%
“… In this figure, a hierarchical approach from peptide to peptidomimetic is resumed. ( A ) From SMAMPs [ 219 ]: a peptide scaffold was used to investigate the effect of halogenation and hydrophobicity. ( B ) Summary of SAR for peptidomimetics [ 220 ].…”
Section: Figures Schemes and Tablesmentioning
confidence: 99%
“…So far, fluorination has received the most interest, though the studies tackling the link between fluorination and antimicrobial activity have led to somewhat inconclusive results. For example, introduction of hexafluoroleucine into magainin and buforin conferred enhanced antimicrobial activity and retained low hemolytic properties, while the presence of fluorine atoms and trifluoromethyl groups improved the potency of short cationic peptides 15 17 . By contrast, incorporation of hexafluoroleucine into protegrin analogs led to decreased potency, while lipopeptides with fluorinated tails demonstrated moderate antibacterial activity combined with pronounced hemolytic properties 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The biological studies showed that many of them exhibited more powerful inhibitory activities than the related α‐type natural product. In 2018, Paulsen et al developed a series of cyclic tetrapeptides containing one β 2 ‐amino acid in the sequence (Figure B). Low toxicity and high antimicrobial activity of these potent peptides suggested that the β 2 ‐amino acid containing scaffold was valuable for further design of novel antimicrobial agents.…”
Section: Strategies To Develop Cyclic Peptides Into Therapeutic Agentsmentioning
confidence: 99%